Структурні зміни господарства Північної Буковини наприкінці ХХ - поч. ХХІ ст. - Клим, С. (Культура народов Причерноморья, 2003)
Structural changes of Northern Bukovyna’s economy are dealt with, the changes of the latest XX – eth century. Studied are inter-sphere structural changes in agriculture, industry, services and transport.